The Effectiveness of Poverty Alleviation Programs in Bogor Regency (Case Study TKPKD, P3KE, and RB Tematik Program) - Lugina, Sammy (KnE Social Sciences, 2025)
This study evaluates the effectiveness of government programs in Kabupaten Bogor aimed at poverty alleviation, focusing specifically on the Tim Koordinasi Penanggulangan Kemiskinan Daerah (TKPKD), Program Pemberdayaan Masyarakat Terpadu (P3KE), and Program Pembangunan Daerah Tematik (RB Tematik). By analyzing the implementation, outcomes, and challenges of these programs, this research assesses their impact on reducing poverty levels within the region. A qualitative approach is used, combined with a case study method. The study highlights the successes and shortcomings of these initiatives, offering insights into their overall effectiveness and suggesting potential improvements. The findings indicate that while these programs have contributed to poverty reduction, there are areas requiring enhancement to maximize their benefits and reach.